The role of trust in SMEs financing by participative banks: an exploratory study in the Moroccan context - FELLAH Sara; BENSBAHOU Aziz (African Scientific Journal, 2024)
Abstract : Participative banks face significant distinctive risks, due to the specificity of their intermediation model and products. SME financing represents a high risk for these banks, because of the informational opacity and lack of visibility that characterize this category of company. The insufficiency of objective data for risk assessment has led researchers to introduce other subjective elements. This involves taking into account the social interactions between the banker and the company manager, creating a certain psychological comfort that facilitates communication and coordination between the two parties, and thus the building trust on both sides. The lack of research on the role of trust in the bank financing relationship in general, and in the context of participative banking in particular, leads us to adopt an exploratory approach. The aim of our study is to discover how trust (which can be built in the banking relationship) can impact the conditions of SME financing by participative banks in the Moroccan context. The questions concerned financing through Mourabaha, the only product offered by Moroccan participative banks. Semi-structured interviews with branch managers and bank advisors revealed that trust in the participative financing relationship has five determinants: the duration of the relationship, the interaction with the company manager, the perception of his competence, benevolence and integrity. The results also showed that trust has a positive impact on the financing conditions (access, cost, guarantee) granted by participative banks to SMEs. Keywords: SMEs, participative banking, trust